Trombe wall for a residential building in Sichuan-Tibet alpine valley – A case study. (August 2020) - Zhang, Lili; Hou, Yuyao; Liu, Zu'an; Du, Junfei; Xu, Long; Zhang, Guomin; Shi, Long
Abstract: Trombe wall (also called T-Wall) as a reliable renewable energy system has attracted increasing attention from both academics and engineers under the current energy crisis. This study then focused on a Tibetan dwelling retrofitting in the Sichuan-Tibet Alpine Valley, adopting T-wall as a passive heating solution. We investigated a classic T-wall in the target building based on field measurement, orthogonal experiment, and numerical simulation methods. It was known that the maximum average indoor temperature of the master room can reach 18.87 °C in the coldest month (January) of the Sichuan-Tibet Alpine Valley. Six key influencing factors were analyzed accordingly, including the south T-wall-to-wall ratio, inlet/outlet height, glazing inclination angle, storage wall thickness, storage wall material and cavity gap. Among those analyzed factors, it was obtained that the highly significant factors are the south T-wall-to-wall ratio and glazing inclination angle. The larger the proportion of the south T-wall-to-wall ratio, the better the indoor temperature is. The best glazing inclination angle was obtained as 10 0 for the target residential building under the local conditions. Solar passive technology as a cost-effective solution can improve the indoor thermal environment of the Tibetan dwellings in the Qinghai-Tibet Plateau. The total annual energy consumption of the Tibetan dwelling using the optimal combination can be reduced by about 72% compared to that of the existing Tibetan houses. The research outcomes can provide a practical guide on the future design of passive solar technologies. Highlights: A case study on Trombe wall was taken in a building in Sichuan-Tibet Alpine Valley. The maximum average indoor temperature can reach 18.87 °C in the coldest month. The significant factors are south T-wall-to-wall ratio and glazing inclination angle. The best glazing inclination angle was obtained as 10 0 under the local conditions. The optimal combination can about 72% energy compared to the existing Tibetan houses.